Re‐evaluation of certain aspects of the EFSA Scientific Opinion of April 2010 on risk assessment of parasites in fishery products, based on new scientific data. Part 1: ToRs1–3 - EFSA Panel on Biological Hazards (BIOHAZ); Konstantinos Koutsoumanis; Ana Allende; Avelino Alvarez‐Ordóñez; Sara Bover‐Cid; Marianne Chemaly; Alessandra De Cesare; Lieve Herman; Friederike Hilbert; Roland Lindqvist; Maarten Nauta; Romolo Nonno; et al. (EFSA Journal)
Abstract Surveillance data published since 2010, although limited, showed that there is no evidence of zoonotic parasite infection in market quality Atlantic salmon, marine rainbow trout, gilthead seabream, turbot, meagre, Atlantic halibut, common carp and European catfish. No studies were found for greater amberjack, brown trout, African catfish, European eel and pikeperch. Anisakis pegreffii, A. simplex (s. s.) and Cryptocotyle lingua were found in European seabass, Atlantic bluefin tuna and/or cod, and Pseudamphistomum truncatum and Paracoenogonimus ovatus in tench, produced in open offshore cages or flow‐through ponds or tanks. It is almost certain that fish produced in closed recirculating aquaculture systems (RAS) or flow‐through facilities with filtered water intake and exclusively fed heat‐treated feed are free of zoonotic parasites. Since the last EFSA opinion, the UV‐press and artificial digestion methods have been developed into ISO standards to detect parasites in fish, while new UV‐scanning, optical, molecular and OMICs technologies and methodologies have been developed for the detection, visualisation, isolation and/or identification of zoonotic parasites in fish. Freezing and heating continue to be the most efficient methods to kill parasites in fishery products. High‐pressure processing may be suitable for some specific products. Pulsed electric field is a promising technology although further development is needed. Ultrasound treatments were not effective. Traditional dry salting of anchovies successfully inactivated Anisakis. Studies on other traditional processes – air‐drying and double salting (brine salting plus dry salting) – suggest that anisakids are successfully inactivated, but more data covering these and other parasites in more fish species and products is required to determine if these processes are always effective. Marinade combinations with anchovies have not effectively inactivated anisakids. Natural products, essential oils and plant extracts, may kill parasites but safety and organoleptic data are lacking. Advanced processing techniques for intelligent gutting and trimming are being developed to remove parasites from fish.